Antifungals patterns in critical patients with candidiasis in the intensive care units at Sanglah General Hospital 2019 - Komang Ady Widayana; I Wayan Aryabiantara; Tjokorda Gde Agung Senapathi; I Wayan Suranadi; I Gusti Ngurah Mahaalit Aribawa (Indoscholar, 2019)
Abstract Introduction: The prompt initiation of appropriate antifungal therapy is essential in controlling invasive candidiasis and improving the prognosis in critical patients undergoing treatment in the Intensive Care Unit. Candida Score can assess patients at risk of candidiasis and is expected to assist clinicians in starting antifungal therapy in patients suspected Candidiasis. The purpose of this study was to determine the pattern of antifungal administration in critically ill patients with candidiasis in the Intensive Care Unit at Sanglah General Hospital. Patients and Methods: The design of this study is a cross-sectional descriptive study involving critically ill patients who were under treatment in Intensive Care Unit of Sanglah General Hospital from Januari to June 2019. The patients included in this study were patients who were ≥ 18 years old and under treatment in ICU for at least 7 days. Results: There are 64 patients undergoing treatment in the Intensive Care Unit. From 64 patients, 6 pasien had CS = 0, 29 patients had CS = 1, 13 patients had CS = 2, 11 patients had CS = 3, 5 patients had CS = 4, and no patients had CS = 5. Eleven patients received empirical antifungal therapy. All empirical antifungal therapies use the Triazole group. Conclusion: In this study was found that 11 of 16 patients with a CS value of ≥ 2.5 were given empirical antifungal therapy, while 48 patients with a CS value of <2.5 were not given empirical antifungal therapy. Keywords: Invasive Candidiasis, Candida Score, Empirical Antifungal Therapy.